Ecological and genetic diversity of plant growth-promoting genes in rhizobacteria isolated from the rhizosphere of wild flora on Mount Erciyes, Türkiye - Azizoglu, Ugur (Frontiers in Plant Science, 2025)
IntroductionThis study is the first to investigate the genetic diversity of plant growth-promoting genes in rhizobacteria isolated from the wild ecology of Mount Erciyes, Türkiye. It has a flora rich in flowering plants, with 1170 plant taxa, 194 of which are endemic to the area.MethodsA total of 165 bacterial isolates, including Azotobacter sp., Azospirillum sp., and Bacillus sp., were screened for genes associated with plant growth promotion: nitrogen fixation (nif), indole pyruvate decarboxylase (ipdC), 1-aminocyclopropane-1-carboxylate deaminase (accd), phosphate-solubilizing genes (Acpho, Alpho and phy), and siderophore biosynthesis (sd).ResultsThe analysis revealed significant genetic variability across isolates, particularly for nif and sd genes, with distinct band patterns indicating genetic diversity among Azospirillum and Bacillus isolates.DiscussionThe findings emphasize the role of these rhizobacteria in nutrient cycling and stress resilience, potentially enhancing plant growth in nutrient-limited soils. In the current study, it contributes to understanding microbial biodiversity in Mount Erciyes and suggests a promising potential for sustainable agriculture through plant-microbe interactions.